ANALISIS FAKTOR LINGKUNGAN FISIK DALAM RUANG YANG BERHUBUNGAN DENGAN KEJADIAN TUBERKULOSIS PARU DI NEGARA BERKEMBANG - Sriratih, Eldrajune Agnes; Suhartono, Suhartono; Nurjazuli, Nurjazuli (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
One of all the contributing factors of Tuberculosis cases is environmental factors. So many cases of Tuberculosis are found in developing countries. Developing countries still have some issues or problems with environmental or living conditions. For example, in Indonesia, which takes the third place in Tuberculosis cases based on the World Health Organization in 2018, there are problems with sanitation and living conditions that are not well in some provinces in Indonesia. Based on those reasons, this review aims to describe what's the factor that influences the incidence of Tuberculosis. Systematic Review used in this research based on the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) guidelines. Articles reviewed took from some international database and national database. For the international database there are 5 databases, those are NCBI (MEDLINE/PubMed), Science Direct, Scopus, Springer Link, JSTOR and for national databases are Portal SINTA and Garuda Rujukan Digital. Based on 11 articles reviewed, 7 factors associated with Tuberculosis cases found, those are overcrowding, structure and material of building, temperature, lighting, dampness, and cooking fuel. Density of occupancy or overcrowding and the presence of ventilation are factors of the physical environment that are often found. Those factors are related to the income level of their population in each country. In developing country income level leads to the fact that people didn’t have so many sources, especially material to build a good building. A bad structure or quality of the building leads to other environmental factors such as overcrowding also the presence and the functions of ventilation associated with temperature, lighting and dampness.